Answer:
Step-by-step :
Your answer
Your answer
9.75
Mark it as Brainlist answer. Follow me.
Mark it as Brainlist answer. Follow me.
Answer:
The values for expression is h = - 2 and k = 5
Step-by-step explanation:
Given algebraic expression can be written as :
2 x³ - 10 x² + 11 x - 7 = ( x - 4 ) × ( 2 x² + h x + 3 ) + k
Now opening the bracket
Or, 2 x³ - 10 x² + 11 x - 7 = x × ( 2 x² + h x + 3 ) - 4 × ( 2 x² + h x + 3 ) + k
Or, 2 x³ - 10 x² + 11 x - 7 = 2 x³ + h x² + 3 x - 2 x² - 4 h x - 12 +k
Or , 2 x³ - 10 x² + 11 x - 7 = 2 x³ + ( h - 2 ) x² + ( 3 - 4 h ) x - 12 + k
Now, equating the equation both sides
I.e - 10 = ( h - 2 )
Or , h - 2 = - 10
I.e , h = - 10 + 2
∴ h = - 2
Again , 11 = ( 3 - 4 h )
or, 11 = 3 - 4 h
or, 11 - 3 = - 4 h
or, 8 = - 4 h
∴ h = 
I.e h = - 2
Again
- 7 = - 12 + k
Or, k = - 7 + 12
∴ k = 5
Hence The values for expression is h = - 2 and k = 5 . Answer
Answer: 67.27
Step-by-step explanation:
7.1 x 7.1 for the square = 50.41
7.1 divided by 2 = 3.55
3.55 x 4.75= 16.86
Normally here you would divide by 2, but you don’t need two because there is 2 triangles that are the same
Add the 50.41 and the 16.86 and you have your answer!
Answer:
-32p +56
Step-by-step explanation:
distribute the 8 to everything in the parenthesis